2014
DOI: 10.1155/2014/835179
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Volumetric Modulated Arc Therapy, Static Field Intensity Modulated Radiation Therapy, and 3D Conformal Planning for the Treatment of a Right-Sided Reconstructed Chest Wall and Regional Nodal Case

Abstract: We compared 3D conformal planning, static field intensity modulated radiation therapy (IMRT), and volumetric modulated arc therapy (VMAT) to investigate the suitable treatment plan and delivery method for a right-sided reconstructed chest wall and nodal case. The dose prescribed for the reconstructed chest wall and regional nodes was 50.4 Gy. Plans were compared for target coverage and doses of the lungs, heart, contralateral breast, and healthy tissue. All plans achieved acceptable coverage of the target and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(32 reference statements)
1
6
1
Order By: Relevance
“…A low average dose to the contralateral breast was one of the priorities during the optimization of the VMAT plans in our study, and the mean dose of the patient population was 2.6 Gy for this technique. This dose was significantly higher than the contralateral breast dose in our 3DCRT plans, nonetheless, it is in the same order as Johansen et al and Dumane et al reported in their VMAT studies [38,39]. Overall survival in breast cancer patients has been significantly improved and therefore the dose to normal tissue should be kept as low as possible.…”
Section: Discussionsupporting
confidence: 62%
“…A low average dose to the contralateral breast was one of the priorities during the optimization of the VMAT plans in our study, and the mean dose of the patient population was 2.6 Gy for this technique. This dose was significantly higher than the contralateral breast dose in our 3DCRT plans, nonetheless, it is in the same order as Johansen et al and Dumane et al reported in their VMAT studies [38,39]. Overall survival in breast cancer patients has been significantly improved and therefore the dose to normal tissue should be kept as low as possible.…”
Section: Discussionsupporting
confidence: 62%
“…This was in contrast with the results published by Severin et al, but consistent with the findings of a more recent study by Dumane et al in 2014 (17, 22). In the latter study, the V95% for the target, which included the chest wall and the nodes, was > 95% for both the PWT and photon/electron techniques (22). Nonetheless, the highest V95% observed in our study was 94.5% in BCS patients treated with the P/E plan.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous studies have been inconclusive regarding the superiority of a specific technique in causing less radiation-induced toxicity. Some studies have shown that the PWT technique leads to an increased depth of normal tissue exposed to radiation and, thus, have proposed that using a combination of photons and electrons could significantly decrease the amount of lung and heart exposure to high-dose radiation (17,22,24). On the other side, several studies indicated that cardiac substructures receive more radiation exposure after radiotherapy with a P/E beam and the least exposure with PWT (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Intensity modulated radiation therapy (IMRT) has demonstrated improved ipsilateral lung sparing at moderate and high doses and a better conformal index (CI) for breast cancer and nodal irradiation compared with 3DCRT. 1,2 Although there are many published dosimetric studies investigating modulated beams for breast cancer treatment, [3][4][5][6][7][8][9][10][11] few discuss how to account for skin flashing when using inverse optimized modulated beams and the effectiveness of these techniques. The breast is a highly mobile structure for which setup reproducibility is poor, which can lead to suboptimal dose distributions and variations from the expected dosimetry if the geometry error is not properly accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…The breast is a highly mobile structure for which setup reproducibility is poor, which can lead to suboptimal dose distributions and variations from the expected dosimetry if the geometry error is not properly accounted for. 12 In current clinical practice, the methods for adequate coverage of the "flash region" for breast IMRT plans include (1) optimization on the nominal planning target volume (PTV; planning target not extending beyond the skin) and manually opening the multi-leaf collimator (MLC) and jaw for flash; (2) adding an artificial bolus in the PTV region outside of the skin during optimization or optimization on an expanded PTV beyond the skin 13,14 ; and (3) optimization on the nominal PTV followed by an expansion of the fluence outside of the skin using a "skinflash tool." 15 Though this third approach of using a "skinflash tool" is supported by the Eclipse treatment planning system (TPS; Varian Medical Systems, Inc, Palo Alto, CA), it is not very straightforward for centers using any other TPS.…”
Section: Introductionmentioning
confidence: 99%